Formação continuada de professores: a JEIF na construção das territorialidades docentes em uma escola pública do município de São Paulo - Figueiredo, Tayna Mota Santos [UNIFESP] (2019)
The present research aims at understanding the territoriality of teachers that elementary school teachers (early years) establish with the Integral Special Day of Formation of a public school in the city of São Paulo, located in a peripheral place. Thus, with JEIF as the object of study, it is sought to observe it from the point of view of the teacher and to understand how, through this public policy of formation, the teachers construct links with the school, family and students. The methodological course of this work is marked by the qualitative approach. Being this, a case study, the research was unfolded to investigate a single municipal school of São Paulo having as data collection instrument the semistructured interviews and the observation. The analysis of the data collected by the research was done through content analysis (Bardin, 2004). The theoretical reference of the research sought to contemplate discussions about teacher training from the contributions of Bernadette Gatti (2010), Demerval Saviani (2009) and José Carlos Libâneo (2016). Regarding the permanent formation, the dissertation spoke the author Francisco Imbernón (2011). The research is based on the work of Algebaile (2009), Bresser-Pereira (1998), Carnoy (1986), Cavalcanti (2008), Mészáros (2008), Saraiva (2015) and Thin (2006). The results indicate that the JEIF exerts influence on the relations between teachers and school, teachers and students, teachers and families and interferes in the construction of the teaching territorialities of elementary school teachers of a municipal school located in a peripheral place.